Probing three-dimensional surface force fields with atomic resolution: Measurement strategies, limitations, and artifact reduction - Baykara, M.Z.; Dagdeviren, O.E.; Schwendemann, T.C.; Mönig, H.; Altman, E.I.; Schwarz, U.D. (Beilstein Journal of Nanotechnology, 2012)
Noncontact atomic force microscopy (NC-AFM) is being increasingly used to measure the interaction force between an atomically sharp probe tip and surfaces of interest, as a function of the three spatial dimensions, with picometer and piconewton accuracy. Since the results of such measurements may be affected by piezo nonlinearities, thermal and electronic drift, tip asymmetries, and elastic deformation of the tip apex, these effects need to be considered during image interpretation. In this paper, we analyze their impact on the acquired data, compare different methods to record atomic-resolution surface force fields, and determine the approaches that suffer the least from the associated artifacts. The related discussion underscores the idea that since force fields recorded by using NC-AFM always reflect the properties of both the sample and the probe tip, efforts to reduce unwanted effects of the tip on recorded data are indispensable for the extraction of detailed information about the atomicscale properties of the surface. © 2012 Baykara et al.
Keywords: Artifact reduction; Atomic force microscopy; Atomic scale; Atomic-resolution; Elasticity; Electronic drift; Force fields; Force spectroscopy; Image interpretation; Interaction forces; Measurement strategies; NC-AFM; Noncontact atomic force microscopy; Probe tips; Spatial dimension; Surface forces; Three dimensional; Three-dimensional atomic force microscopy; Three-dimensional surface; Tip apex; Tip asymmetry; Tip elasticity; dept.phy

The effectiveness of multimedia and activity-based supplemental teaching resources in materials science education - Day, D.A.; Abbasi, E.; Liang, B.; Bhat, S.; DeMeo, S.; Garofano, J.; Grober, L.; Ferrari, N.; Broadbridge, C. (2012)
A comparative study investigating the integration of supplemental teaching resources in materials science education was developed for the purpose of determining the effectiveness of teaching strategies. Digital stories created by students, excerpts from the Nova Making Stuff documentaries, YouTube educational videos and student generated demo-kits were used as part of the investigation whereby two 9th grade science classes (n∼26) were evaluated. Each participant in the study received one period (40-min) of a traditional lesson on Materials Science including specific content, vocabulary, and a pre- and post- lesson assessment. Additionally, the students in each class participated in a 30-min supplemental component, e.g. video or activity-based demonstration using aforementioned kits or video compilation. Pre- and post- evaluations (e.g. open-ended and likert questions) were administered to all of the participants. As hypothesized, the students' feedback and performance on assessment activities reveal that the use of multimedia and activity-based resources may be equally effective teaching methods as traditional methods. © 2012 Materials Research Society.
Keywords: Activity-based; Assessment activities; Comparative studies; Educational videos; Effective teaching methods; Materials science; Multimedia systems; Students; Teaching resources; Teaching strategy; YouTube; dept.phy

Speckle camera imaging of the planet Pluto - Howell, S.B.; Horch, E.P.; Everett, M.E.; Ciardi, D.R. (Publications of the Astronomical Society of the Pacific, 2012)
We have obtained optical wavelength (692 nm and 880 nm) speckle imaging of the planet Pluto and its largest moon Charon. Using our DSSI speckle camera attached to the Gemini North 8 m telescope, we collected high resolution imaging with an angular resolution of ~20 mas, a value at the Gemini-N telescope diffraction limit. We have produced for this binary system the first speckle reconstructed images, from which we can measure not only the orbital separation and position angle for Charon, but also the diameters of the two bodies. Our measurements of these parameters agree, within the uncertainties, with the current best values for Pluto and Charon. The Gemini-N speckle observations of Pluto are presented to illustrate the capabilities of our instrument and the robust production of high accuracy, high spatial resolution reconstructed images. We hope our results will suggest additional applications of high resolution speckle imaging for other objects within our solar system and beyond. © 2012. The Astronomical Society of the Pacific. All rights reserved.
Keywords: dept.phy; peer-reviewed

Observations of binary stars with the differential speckle survey instrument. iv. observations of kepler, corot, and hipparcos stars from the gemini north telescope - Horch, Elliott P.; Howell, Steve B.; Everett, Mark E.; Ciardi, David R. (The Astronomical Journal, 2012)
We present the results of 71 speckle observations of binary and unresolved stars, most of which were observed with the DSSI speckle camera at the Gemini North Telescope in 2012 July. The main purpose of the run was to obtain diffraction-limited images of high-priority targets for the Kepler and CoRoT missions, but in addition, we observed a number of close binary stars where the resolution limit of Gemini was used to better determine orbital parameters and/or confirm results obtained at or below the diffraction limit of smaller telescopes. Five new binaries and one triple system were discovered, and first orbits are calculated for other two systems. Several systems are discussed in detail. © 2012. The American Astronomical Society. All rights reserved..
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Exploring atomic-scale lateral forces in the attractive regime: a case study on graphite (0001) - Baykara, Mehmet Z.; Schwendemann, Todd C.; Albers, Boris J.; Pilet, N.; Mönig, Harry; Altman, Eric I.; Schwarz, Udo D. (Nanotechnology, 2012)
A non-contact atomic force microscopy-based method has been used to map the static lateral forces exerted on an atomically sharp Pt/Ir probe tip by a graphite surface. With measurements carried out at low temperatures and in the attractive regime, where the atomic sharpness of the tip can be maintained over extended time periods, the method allows the quantification and directional analysis of lateral forces with piconewton and picometer resolution as a function of both the in-plane tip position and the vertical tip-sample distance, without limitations due to a finite contact area or to stick-slip-related sudden jumps of tip apex atoms. After reviewing the measurement principle, the data obtained in this case study are utilized to illustrate the unique insight that the method offers. In particular, the local lateral forces that are expected to determine frictional resistance in the attractive regime are found to depend linearly on the normal force for small tip-sample distances. © 2012 IOP Publishing Ltd.
Keywords: Atomic force; Atomic force microscopy; Atomic scale; Contact areas; Directional Analysis; Frictional resistance; Graphite; Graphite surfaces; Lateral force; Low temperatures; Measurement principle; Non-contact; Normal forces; Picometer resolution; Probe tips; Slip forming; Time-periods; Tip apex; Tip-sample distance; dept.phy

Transit timing observations from kepler. II. confirmation of two multiplanet systems via a non-parametric correlation analysis - Ford, Eric B.; Fabrycky, Daniel C.; Steffen, Jason H.; Carter, Joshua A.; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Morehead, Robert C.; Ragozzine, Darin; Rowe, Jason F.; Welsh, William F.; et al. (The Astrophysical Journal, 2012)
We present a new method for confirming transiting planets based on the combination of transit timing variations (TTVs) and dynamical stability. Correlated TTVs provide evidence that the pair of bodies is in the same physical system. Orbital stability provides upper limits for the masses of the transiting companions that are in the planetary regime. This paper describes a non-parametric technique for quantifying the statistical significance of TTVs based on the correlation of two TTV data sets. We apply this method to an analysis of the TTVs of two stars with multiple transiting planet candidates identified by Kepler. We confirm four transiting planets in two multiple-planet systems based on their TTVs and the constraints imposed by dynamical stability. An additional three candidates in these same systems are not confirmed as planets, but are likely to be validated as real planets once further observations and analyses are possible. If all were confirmed, these systems would be near 4:6:9 and 2:4:6:9 period commensurabilities. Our results demonstrate that TTVs provide a powerful tool for confirming transiting planets, including low-mass planets and planets around faint stars for which Doppler follow-up is not practical with existing facilities. Continued Kepler observations will dramatically improve the constraints on the planet masses and orbits and provide sensitivity for detecting additional non-transiting planets. If Kepler observations were extended to eight years, then a similar analysis could likely confirm systems with multiple closely spaced, small transiting planets in or near the habitable zone of solar-type stars. © 2012. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; planets and satellites: detection; planets and satellites: dynamical evolution and stability; stars: individual (KIC 3231341, 11512246, KOI 168, 1102, Kepler-23, Kepler-24); techniques: miscellaneous

Kepler-20: a sun-like star with three sub-neptune exoplanets and two earth-size candidates - Gautier, Thomas N.; Charbonneau, David; Rowe, Jason F.; Marcy, Geoffrey W.; Isaacson, Howard; Torres, Guillermo; Fressin, Francois; Rogers, Leslie A.; Désert, Jean-Michel; Buchhave, Lars A.; Latham, David W.; Quinn, Samuel N.; et al. (The Astrophysical Journal, 2012)
We present the discovery of the Kepler-20 planetary system, which we initially identified through the detection of five distinct periodic transit signals in the Kepler light curve of the host star 2MASS J19104752+4220194. From high-resolution spectroscopy of the star, we find a stellar effective temperature T eff = 5455 100 K, a metallicity of [Fe/H] = 0.01 0.04, and a surface gravity of log g = 4.4 0.1. We combine these estimates with an estimate of the stellar density derived from the transit light curves to deduce a stellar mass of M = 0.912 0.034 M and a stellar radius of R = 0.944 +0.060 -0.095 R. For three of the transit signals, we demonstrate that our results strongly disfavor the possibility that these result from astrophysical false positives. We accomplish this by first identifying the subset of stellar blends that reproduce the precise shape of the light curve and then using the constraints on the presence of additional stars from high angular resolution imaging, photometric colors, and the absence of a secondary component in our spectroscopic observations. We conclude that the planetary scenario is more likely than that of an astrophysical false positive by a factor of 2 × 105 (Kepler-20b), 1 × 105 (Kepler-20c), and 1.1 × 103 (Kepler-20d), sufficient to validate these objects as planetary companions. For Kepler-20c and Kepler-20d, the blend scenario is independently disfavored by the achromaticity of the transit: from Spitzer data gathered at 4.5 μm, we infer a ratio of the planetary to stellar radii of 0.075 0.015 (Kepler-20c) and 0.065 0.011 (Kepler-20d), consistent with each of the depths measured in the Kepler optical bandpass. We determine the orbital periods and physical radii of the three confirmed planets to be 3.70days and 1.91+0.12 -0.21 R ⊕ for Kepler-20b, 10.85days and 3.07+0.20 -0.31 R ⊕ for Kepler-20c, and 77.61days and 2.75+0.17 -0.30 R ⊕ for Kepler-20d. From multi-epoch radial velocities, we determine the masses of Kepler-20b and Kepler-20c to be 8.7 2.2 M ⊕ and 16.1 3.5 M ⊕, respectively, and we place an upper limit on the mass of Kepler-20d of 20.1 M ⊕ (2σ). © 2012 The American Astronomical Society. All rights reserved.
Keywords: dept.phy; eclipses; planetary systems

Transit timing observations from kepler: III. confirmation of 4 multiple planet systems by a fourier-domain study of anti-correlated transit timing variations - Steffen, Jason H.; Fabrycky, Daniel C.; Ford, Eric B.; Carter, Joshua A.; Désert, Jean-Michel; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Rowe, Jason F.; Ragozzine, Darin; Welsh, William F.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
We present a method to confirm the planetary nature of objects in systems with multiple transiting exoplanet candidates. This method involves a Fourier-domain analysis of the deviations in the transit times from a constant period that result from dynamical interactions within the system. The combination of observed anticorrelations in the transit times and mass constraints from dynamical stability allow us to claim the discovery of four planetary systems, Kepler-25, Kepler-26, Kepler-27 and Kepler-28, containing eight planets and one additional planet candidate. © 2012 Fermi Research Alliance LLC, Contractor for the U.S. Dept of Energy Monthly Notices of the Royal Astronomical Society © 2012 RAS.
Keywords: Celestial mechanics; Methods: data analysis; Stars: individual: KIC 4349452; Stars: individual: KIC 5792202; Stars: individual: KIC 6949607; Stars: individual: KIC 9757613; dept.phy; peer-reviewed

KEPLER-21b: A 1.6 REarth planet transiting the bright oscillating F subgiant star HD179070 - Howell, Steve B.; Rowe, Jason F.; Bryson, Stephen T.; Quinn, Samuel N.; Marcy, Geoffrey W.; Isaacson, Howard; Ciardi, David R.; Chaplin, William J.; Metcalfe, Travis S.; Monteiro, Mário J. P. F. G.; Appourchaux, Thierry; Basu, Sarbani; et al. (The Astrophysical Journal, 2012)
We present Kepler observations of the bright (V = 8.3), oscillating star HD179070. The observations show transit-like events which reveal that the star is orbited every 2.8days by a small, 1.6 R Earth object. Seismic studies of HD179070 using short cadence Kepler observations show that HD179070 has a frequency-power spectrum consistent with solar-like oscillations that are acoustic p-modes. Asteroseismic analysis provides robust values for the mass and radius of HD179070, 1.34 ± 0.06 M ⊙ and 1.86 ± 0.04 R ⊙, respectively, as well as yielding an age of 2.84 ± 0.34Gyr for this F5 subgiant. Together with ground-based follow-up observations, analysis of the Kepler light curves and image data, and blend scenario models, we conservatively show at the >99.7% confidence level (3σ) that the transit event is caused by a 1.64 0.04 R Earth exoplanet in a 2.785755 ± 0.000032day orbit. The exoplanet is only 0.04 AU away from the star and our spectroscopic observations provide an upper limit to its mass of ∼10 M Earth (2σ). HD179070 is the brightest exoplanet host star yet discovered by Kepler. © 2012. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: activity; stars: individual (HD 179070: KIC 3632418); stars: interiors; stars: late-type; stars: magnetic field; stars: oscillations (including pulsations); techniques: photometric

Positive attitudinal shifts with the physics by inquiry curriculum across multiple implementations - Lindsey, Beth A; Hsu, Leonardo; Sadaghiani, Homeyra R; Taylor, Jack W; Cummings, Karen (Physical Review Special Topics - Physics Education Research, 2012)
Recent publications have documented positive attitudinal shifts on the Colorado Learning Attitudes about Science Survey (CLASS) among students enrolled in courses with an explicit epistemological focus. We now report positive attitudinal shifts in classes using the Physics by Inquiry (PbI) curriculum, which has only an implicit focus on student epistemologies and nature of science issues. These positive shifts have occurred in several different implementations of the curriculum, across multiple institutions and multiple semesters. In many classes, students experienced significant attitudinal shifts in the problem-solving categories of the CLASS, despite the conceptual focus of most PbI courses.
Keywords: dept.phy

Kepler-22b: A 2.4 Earth-radius Planet in the Habitable Zone of a Sun-like Star - Borucki, William J.; Koch, David G.; Batalha, Natalie M.; Bryson, Stephen T.; Rowe, Jason F.; Fressin, Francois; Torres, Guillermo; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2012)
A search of the time-series photometry from NASA's Kepler spacecraft reveals a transiting planet candidate orbiting the 11th magnitude G5 dwarf KIC 10593626 with a period of 290 days. The characteristics of the host star are well constrained by high-resolution spectroscopy combined with an asteroseismic analysis of the Kepler photometry, leading to an estimated mass and radius of 0.970 0.060 M and 0.979 0.020 R. The depth of 492 10 ppm for the three observed transits yields a radius of 2.38 0.13 Re for the planet. The system passes a battery of tests for false positives, including reconnaissance spectroscopy, high-resolution imaging, and centroid motion. A full BLENDER analysis provides further validation of the planet interpretation by showing that contamination of the target by an eclipsing system would rarely mimic the observed shape of the transits. The final validation of the planet is provided by 16 radial velocities (RVs) obtained with the High Resolution Echelle Spectrometer on Keck I over a one-year span. Although the velocities do not lead to a reliable orbit and mass determination, they are able to constrain the mass to a 3σ upper limit of 124 M ⊕, safely in the regime of planetary masses, thus earning the designation Kepler-22b. The radiative equilibrium temperature is 262 K for a planet in Kepler-22b's orbit. Although there is no evidence that Kepler-22b is a rocky planet, it is the first confirmed planet with a measured radius to orbit in the habitable zone of any star other than the Sun. © 2012. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: fundamental parameters; stars: individual (Kepler-22, KIC 10593626)

Portable intensity interferometry - Horch, Elliott P; Camarata, Matthew A (2012)
A limitation of the current generation of long baseline optical interferometers is the need to make the light interfere prior to detection. This is unlike the radio regime where signals can be recorded fast enough to use electronics to accomplish the same result. This paper describes a modern optical intensity interferometer based on electronics with picosecond timing resolution. The instrument will allow for portable optical interferometry with much larger baselines than currently possible by using existing large telescopes. With modern electronics, the limiting magnitude of the technique at a 4-m aperture size becomes competitive with some amplitude-based interferometers. The instrumentation will permit a wireless mode of operation with GPS clocking technology, extending the work to extremely large baselines. We discuss the basic observing strategy, a planned observational program at the Lowell Observatory 1.8-m and 1.0-m telescopes, and the science that can realistically be done with this instrumentation. © 2012 SPIE.
Keywords: Aperture sizes; Binary star; Binary stars; Current generation; Intensity interferometry; Interferometers; Interferometry; Large telescopes; Long base line; Mode of operations; Optical intensities; Optical interferometer; Optical interferometry; Optical telescopes; Picosecond timing; Single photon avalanche diode; Single photon avalanche diodes; Stars; Stellar disks; Stellar radii; Telescopes; dept.phy

The infrared light curve of SN 2011fe in m101 and the distance to m101 - Matheson, Thomas; Joyce, Richard R; Allen, Lori E; Saha, A; Silva, David R; Woodvasey, W M; Adams, Joshua J; Anderson, R E; Beck, Tracy L; Bentz, Misty C; Bershady, Matthew A; Binkert, W S; et al. (The Astrophysical Journal, 2012)
We present near-infrared light curves of supernova (SN) 2011fe in M101, including 34 epochs in H band starting 14days before maximum brightness in the B band. The light curve data were obtained with the WIYN High-Resolution Infrared Camera. When the data are calibrated using templates of other Type Ia SNe, we derive an apparent H-band magnitude at the epoch of B-band maximum of 10.85 ± 0.04. This implies a distance modulus for M101 that ranges from 28.86 to 29.17mag, depending on which absolute calibration for Type Ia SNe is used. © © 2012. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; galaxies: distances and redshifts; galaxies: individual (M101); supernovae: individual (SN 2011fe)